Ujian Keimanan dalam Novel Ayat-Ayat Cinta: Analisis Teologis melalui Naratologi Todorov dan Semiotika Barthes - Muhamad Irfan Kurniawan; Zulfa Lutfiyatul Uyun; Mila Aulina Putri; Muhamad Raffael Al Zazilu; Dadan Firdaus (Jurnal Ilmiah Literasi Indonesia, 2026)
This study analyzes the representation of faith (iman) and the concept of monotheism (tawhid) as an existential and liberating guide to facing life's trials in Habiburrahman El Shirazy's novel, Ayat-Ayat Cinta (AAC). This research integrates Islamic theological perspectives (Ilmu Kalam) with contemporary literary criticism: Tzvetan Todorov’s Narratology and Roland Barthes’ Semiotics. The study employs a qualitative descriptive method focusing on textual analysis through Van Dijk's critical discourse framework. Epistemologically, contemporary theological thought demands a paradigm shift from a purely theoretical-doctrinal domain to a practical praxis of human liberation. The results reveal that through Todorov’s narrative structure (equilibrium, disruption, and resolution), the trials of faith experienced by the main character, Fahri, demonstrate a spiritual transformation from static belief to an active theological resilience against systemic injustice. Furthermore, semiotic analysis via Barthes’ three levels of meaning (denotation, connotation, and myth) uncovers that the signs and symbols of suffering reinforce the Islamic ideology of tawhid not merely as an abstract concept of God’s nature, but as an operational framework for enduring social slander and human rights violation. Ultimately, this interdisciplinary integration proves that literary fiction can act as a dynamic medium for contextualizing liberation theology and fostering inclusive, moderate contemporary Islamic thought.